Lower limb stiffness: Effect on performance and training considerations - McMahon, J. J.; Comfort, P.; Pearson, S. (Strength and Conditioning Journal, 2012)
The aim of this review was to summarize the research to date on lower limb stiffness in relation to both its effect on performance and training considerations. Evidence suggests that some amount of lower limb stiffness is required for successful athletic performance, but too much stiffness may be detrimental. To avoid recruiting excessive stiffness, it is suggested that the reactive strength index should be used. In terms of training to increase lower limb stiffness, it is recommended that resistance training should be performed with loads above 75% of 1 repetition maximum and should precede high-intensity plyometric and power training.